Anti-Corruption Culture: Maren and Yelim’s Perspective on Kei Society - Rado, Rudini Hasyim; Betaubun, Restu Monika Nia (SASI, 2023)
Introduction: Controlling corruption by relying too much on a legal approach cannot always be implemented, but what needs to be made effective and efficient is non-law-based prevention efforts through local wisdom approaches.Purposes of the Research: This research is focused on exploring anti-corruption cultural values in the Kei community as an internalization of efforts to prevent corruption where so far similar research has been minimal.Methods of the Research: The type of normative juridical research is then analyzed using qualitative research methods that are oriented towards a value approach and a policy approach. Data were taken from journal literature studies and other scientific works.Results of the Research: The results of the study show that the Maren and/or Yelim praxis can become a forum for togetherness for the Kei people as a fundamental basis for eradicating corrupt behaviour as well as an effort to realize and build anti-corruption integrity values, including, honesty, caring, independence, discipline, responsibility, hard work, modest, brave, and fair.